SILENT REVOLUTION IN NORTHERN SONG: THE POWER LOGIC BEHIND ZUNWANG RANGYI - Xiaobin Huo (History Studies, 2024)
This article examines the formation logic behind the principle of Zunwang Rangyi in early Northern Song dynasty (960－1127) of China. A common interpreting mode for the formation of the theory of Zunwang Rangyi is the externality approach that it’s the threat of military lords and “barbarian” invasion that promoted the formation of the institutional devices based on the principles of Zunwang Rangyi in the Song dynasty. I propose another internality approach by studying how Zunwang Rangyi theory has been transformed in early Northern Song by internally driven factors caused by the Shidafu crisis and how its core principles were mirrored in early Northern Song’s institutional design and state building. With a historical and documentation methodology with a focus on the work of several thinkers of early Northern Song, this research would enrich the current scholarship on the formation and evolution of institutional and state building of early Northern Song and its intellectual background.